Comparative Analysis of The Design Budget for the Asphalt Road Construction of Indraprasta View Pacet Housing with The AHSP Methode with Project Design at PT. Indraprasta Graha Utama - Alfin Hafizh Kholiful Haqiqi; M. Djaelani (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Housing development is a vital sector to improve people's quality of life. Road infrastructure development has a crucial role because it has an impact on property value, comfort, and housing accessibility. Asphalt road development in housing provides benefits in the form of increased accessibility, comfort, and property value. This process includes planning, design, procurement of materials, and construction implementation. In order to find out that the Draft Budget (RAB) for the construction of the Indraprasta View Pacet asphalt road is the maximum, a comparison is made with the calculation of the Draft Budget (RAB) using the AHSP method. The purpose of this research was conducted to find out the comparison of the calculation of the Budget Plan for the construction of asphalt roads for Indraprasta View Pacet housing with calculations using the AHSP method and to find out the factors that influence the differences between the two calculations used and to find out whether the AHSP method can provide benefits in terms of efficiency and effectiveness in calculating the budget for the construction of the Indraprasta View Pacet residential asphalt road. The results obtained from the calculation of the Draft Budget with the RAB profit using the AHSP calculation are 17% and Profit in the Indraprasta Graha Utama RAB is 10%. From this study, the AHSP method obtained a higher profit than the calculation of the Indraprasta Graha Utama Budget Plan. Abstrak Pembangunan perumahan merupakan sektor vital untuk meningkatkan kualitas hidup masyarakat. Pembangunan infrastruktur jalan memiliki peranan yang krusial karena berdampak pada nilai properti, kenyamanan, dan aksesibilitas perumahan. Pengembangan jalan aspal di perumahan memberikan manfaat berupa peningkatan aksesibilitas, kenyamanan, dan nilai properti. Proses ini mencakup perencanaan, desain, pengadaan bahan material, serta pelaksanaan konstruksi. Untuk mengetahui Rancangan Anggaran Biaya (RAB) dari Pembangunan jalan aspal Indraprasta View Pacet tersebut maksimal maka dilakukan perbandingan dengan perhitungan Rancangan Anggaran Biaya (RAB) menggunakan metode AHSP. Tujuan dari penilitian ini dilakukan agar mengetahui perbandingan perhitungan Rancangan Anggaran Biaya pembangunan jalan aspal perumahan indraprasta View Pacet dengan perhitungan mengguanakan metode AHSP dan untuk mengetahui faktor yang mempengaruhi perbedaan dari kedua perhitungan yang digunakan dan untuk mengetahui apakah metode AHSP dapat memberikan keuntungan dari segi efisiensi dan efektivitas dalam perhitungan anggaran biaya pada pembangunan jalan aspal perumahan Indraprasta View Pacet. Hasil yang didapatkan dari perhitungan Rancangan Anggaran Biaya dengan profit RAB menggunakan perhitungan AHSP sebesar 17% dan Profit dalam RAB Indraprasta Graha Utama Sebesar 10%. Dari kajian tersebut, metode AHSP mendapat profit lebih tinggi daripada perhitungan Rancangan Anggaran Biaya Indraprasta Graha Utama.